Holistic Conceptualizations of Health by Incarcerated Aboriginal Women in New South Wales, Australia. (September 2019) - Kendall, Sacha; Lighton, Stacey; Sherwood, Juanita; Baldry, Eileen; Sullivan, Elizabeth
While there has been extensive research on the health and social and emotional well-being (SEWB) of Aboriginal women in prison, there are few qualitative studies where incarcerated Aboriginal women have been directly asked about their health, SEWB, and health care experiences. Using an Indigenous research methodology and SEWB framework, this article presents the findings of 43 interviews with incarcerated Aboriginal women in New South Wales, Australia. Drawing on the interviews, we found that Aboriginal women have holistic conceptualizations of their health and SEWB that intersect with the SEWB of family and community. Women experience clusters of health problems that intersect with intergenerational trauma, perpetuated and compounded by ongoing colonial trauma including removal of children. Women are pro-active about their health but encounter numerous challenges in accessing appropriate health care. These rarely explored perspectives can inform a reframing of health and social support needs of incarcerated Aboriginal women establishing pathways for healing.